Georgia : Russian foreign energy policy and implications for Georgia's energy security - Jervalidze, Liana (Global market briefings., 2006)
Annotation This report shows that as Georgia has restructured its energy sector, the new Russian and Georgian political elites exerted their influence, particularly through the participation of Russian gas company Itera in privatizations of Georgian gas enterprises. And how, over the past few years, Russian-Georgian business groups with their offshore capital have been working to monopolise the Georgian economy and Russia's gas industry has been consolidating its hold over the CIS pipeline infrastructure, particularly through the expansion of Gazprom. However, Gazprom failed to take control of Georgia's pipeline infrastructure and Georgia is insistent on developing its pipeline potential in order to boost its role as a transit route to Europe, Turkey and Iran. Part of the Russian Foreign Energy Policy Report series.